Nursing Problems after Endoscopic Surgery for Benign Prostatic Hyperplasia - Paulikienė, Simona; Rumšienė, Gintarė (Slauga. Mokslas ir praktika, 2024)
Benign prostatic hyperplasia is a common urological conditionin older males. In recent decades, new therapeutic options have evolved in response to the increasing prevalence of benign prostatic hyperplasia. Surgical treatment typically involves standard transurethral resection of the prostate as well as newer techniques such as enucleation of the prostate using a Holmium laser. Swift recognition of nursing issues post-surgery and their resolution aids in minimizing the likelihood of complications and enhancing patients’ mental well-being and overall quality of life. This article examines the nursing issues that occur following endoscopic transurethral resection of the prostate and Holmium laser enucleation of the prostate. The study inlolved 8 nurses from the urology department. Nursing issues following endoscopic transurethral prostate resection and prostate enucleation with Holmium laser were found and compared by data analysis utilizing a semi-structured interview approach. The study revealed that urinary incontinence, headaches, and the danger of infections are common nursing issues following these specific endoscopic procedures. Following transurethral resection of the prostate, there is a risk of hyponatremia due to potential TURP syndrome development, increased likelihood of urinary retention and clot formation in the drainage, and heightened postoperative wound pain. Conversely, after Holmium laser enucleation of the prostate, there is an elevated risk of bleeding and a possibility of retrograde ejaculation.